2022
DOI: 10.2196/38365
|View full text |Cite
|
Sign up to set email alerts
|

An Intervention to Increase Outdoor Play in Early Childhood Education Centers (PROmoting Early Childhood Outside): Protocol for a Pilot Wait-list Control Cluster Randomized Trial

Abstract: Background Participation in outdoor play has been extensively documented as beneficial for the health, well-being, and development of children. Canadian early childhood education centers (ECECs) are important settings in young children’s lives and provide opportunities to participate in outdoor play. However, there are barriers to the provision of outdoor play opportunities at ECECs, such as adverse weather conditions, poorly designed outdoor spaces, outdoor time policies, and early childhood educa… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 63 publications
0
4
0
1
Order By: Relevance
“…Since its development in 2020, the TOPO has been used in different settings, including a recent study of a natural environment adjacent a museum (Loebach & Cox, 2022), early childhood education centres (Ramsden et al, 2022), and community‐led play hubs in parks (Naish et al, 2023). To the authors' knowledge, this is the first use of the TOPO in school outdoor environments in Australia.…”
Section: Methodsmentioning
confidence: 99%
“…Since its development in 2020, the TOPO has been used in different settings, including a recent study of a natural environment adjacent a museum (Loebach & Cox, 2022), early childhood education centres (Ramsden et al, 2022), and community‐led play hubs in parks (Naish et al, 2023). To the authors' knowledge, this is the first use of the TOPO in school outdoor environments in Australia.…”
Section: Methodsmentioning
confidence: 99%
“…A κ value of 0.918 (agreement=95.9%) was achieved prior to beginning data collection. Further information on the PRO-ECO wait-list control randomized control trial and the PRO-ECO intervention can be found in the previously published study protocol (49).…”
Section: Data Collectionmentioning
confidence: 99%
“…Structured play, often facilitated by educators, promotes skill-building, cooperative interactions, and cluster randomized controlled trials (46), the SPIRIT (Standard Protocol Items: Recommendations for Intervention Trials) statement for clinical trial protocols (47) and the evaluation framework of the Medical Research Council (48). The detailed PRO-ECO study protocol has been published (49). Ethics certi cation was received from the University of British Columbia and the Children's and Women's Health Centre of British Columbia Research Ethics Board (H20-03912).…”
Section: Introductionmentioning
confidence: 99%
“…It is important to follow the child’s lead in their expressions of play (E. Stevenson, Personal Communication, 17 November 2022). However, Carmen sought to enhance a more ‘hands on’ and relational emphasis between the educator and the child and possibilities of play to include a more robust focus on active play (without negating the valuable contributions of all types of play for children’s wholistic health and wellness [ 78 , 79 ]) (movement), as role-modeled through early childhood educator efficacy for personal health and wellness in the development of PL [ 80 ].…”
Section: Moment Of Rupture Two—a Break In Social Discoursesmentioning
confidence: 99%